2013
DOI: 10.1080/00224545.2012.757544
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Process Model of Ideology and Prejudice: A Longitudinal Test During a Global Recession

Abstract: This study tested the pathways between personality, social worldviews, and ideology, predicted by the Dual Process Model (DPM) of ideology and prejudice. These paths were tested using a full cross-lagged panel design administered to a New Zealand community sample in early 2008 (before the effects of the global financial crisis reached New Zealand) and again in 2009 (when the crisis was near its peak; n = 247). As hypothesized, low openness to experience predicted residualized change in dangerous worldview, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 41 publications
6
63
0
Order By: Relevance
“…Although such methods cannot rule out alternative explanations of observed effects, longitudinal research also supports the predicted causal pathways in which personality prospectively predicts SDO and RWA (Perry & Sibley, 2012;Sibley & Duckitt, 2010a), dangerous and competitive social worldviews predict SDO and RWA (Sibley, Wilson, & Duckitt, 2007a), and SDO and RWA predict various forms of prejudice (Asbrock, Sibley, & Duckitt, 2010;Sibley & Duckitt, 2010b;Sibley, Wilson, & Duckitt, 2007b). A more comprehensive longitudinal test also recently supported these predicted causal pathways between personality, social worldviews, and ideology (Sibley & Duckitt, 2013).…”
Section: Social and Psychological Bases Of Rwa And Sdomentioning
confidence: 85%
See 1 more Smart Citation
“…Although such methods cannot rule out alternative explanations of observed effects, longitudinal research also supports the predicted causal pathways in which personality prospectively predicts SDO and RWA (Perry & Sibley, 2012;Sibley & Duckitt, 2010a), dangerous and competitive social worldviews predict SDO and RWA (Sibley, Wilson, & Duckitt, 2007a), and SDO and RWA predict various forms of prejudice (Asbrock, Sibley, & Duckitt, 2010;Sibley & Duckitt, 2010b;Sibley, Wilson, & Duckitt, 2007b). A more comprehensive longitudinal test also recently supported these predicted causal pathways between personality, social worldviews, and ideology (Sibley & Duckitt, 2013).…”
Section: Social and Psychological Bases Of Rwa And Sdomentioning
confidence: 85%
“…Research has shown that levels of social threat (e.g., Feldman & Stenner, 1997) and competition (e.g., Dru, 2007;Sibley & Duckitt, 2013) may moderate the associations of RWA and SDO with various outcomes. Recent research has also indicated a number of individual difference factors that potentially moderate these relationships.…”
Section: Caveats and Conclusionmentioning
confidence: 99%
“…Indeed, CWs are not likely to change over time unless “social situations change dramatically in an apparently enduring fashion” (Duckitt & Fisher, , p. 202). Empirical studies confirm this notion and report substantial correlations between CWs measures taken at five‐month ( r = .75) or one‐year ( r = .61) time intervals (Sibley & Duckitt, ; Sibley, Wilson, & Duckitt, ).…”
Section: Introductionmentioning
confidence: 91%
“…Longitudinal studies have shown that the Big Five personality traits predict several facets of religiousness and socio‐political attitudes in terms of RWA and SDO rather than the reverse (Perry & Sibley, ; Sibley & Duckitt, ; Wink et al, ). However, other studies that have used direction‐of‐causation modelling have not supported a directionality from basic traits to socio‐political attitudes but rather point to an interdependence due to common (e.g.…”
Section: Four Criteria Of the Differentiation Between Core And Surfacmentioning
confidence: 99%